Effects of Salinity Stress and ACC Deaminase Sidr Root PGPR Frequency on Growth and Yield of Chili Pepper - Isfiyana, Niza; Nikmatullah, Aluh; Fauzi, M. Taufik (Jurnal Biologi Tropis, 2026)
Salinity stress is a major abiotic factor limiting chili pepper (Capsicum annuum L.) production by reducing water and nutrient uptake and increasing stress-induced ethylene accumulation. Plant Growth-Promoting Rhizobacteria (PGPR) producing 1-aminocyclopropane-1-carboxylate (ACC) deaminase have emerged as a promising biological approach to alleviate salt stress by lowering ethylene levels and promoting plant growth. This study aimed to evaluate the interaction between salinity levels and the application frequency of ACC deaminase-producing PGPR isolated from bidara (Ziziphus mauritiana) roots on chili pepper growth. A factorial randomized complete block design was employed with two factors: salinity levels (0, 2, 4, and 8 dS m⁻¹) and PGPR application frequencies (0, 1, 2, and 3 applications). Data were analyzed using analysis of variance followed by Tukey's HSD test at a 5% significance level. Significant interactions were observed for plant height, leaf number, fresh biomass, root biomass, shoot dry weight, and total dry weight. Increasing salinity significantly reduced plant growth, whereas repeated PGPR application improved vegetative performance. The highest biomass was obtained under non-saline conditions with two PGPR applications, while three applications produced the greatest plant height and leaf number. These findings demonstrate that ACC deaminase-producing PGPR from bidara roots effectively mitigates salinity stress and has potential as an environmentally friendly bioinoculant to improve chili pepper growth under saline conditions.